Evaluating Quercus pollen as a valuable archive of past UV-B levels in the Central Mediterranean: Insights from comparative infrared spectroscopy analyses - H. Saleh; P. Meyvisch; F. Di Rita; A. Spina; G. Margaritelli; D. Magri; M. Ghilardi; M. Alunni Cardinali; A. Di Michele (Review of Palaeobotany and Palynology, 2026)

Benfotiamine Ameliorates Streptozotocin-Induced Alzheimer’s Disease in Rats by Modulating Neuroinflammation, Oxidative Stress, and Microglia - Camila A. E. F. Cardinali; Yandara A. Martins; Ruan C. M. Moraes; Andressa P. Costa; Andréa S. Torrão (Molecular Neurobiology, 2025)

Multi-risk assessment in a historical city - C. Arrighi; M. Tanganelli; M. T. Cristofaro; V. Cardinali; A. Marra; F. Castelli; M. De Stefano (Natural Hazards, 2023)
Natural hazards pose a significant threat to historical cities which have an authentic and universal value for mankind. This study aims at codifying a multi-risk workflow for seismic and flood hazards, for site-scale applications in historical cities, which provides the Average Annual Loss for buildings within a coherent multi-exposure and multi-vulnerability framework. The proposed methodology includes a multi-risk correlation and joint probability analysis to identify the role of urban development in re-shaping risk components in historical contexts. The workflow is unified by exposure modelling which adopts the same assumptions and parameters. Seismic vulnerability is modelled through an empirical approach by assigning to each building a vulnerability value depending on the European Macroseismic Scale (EMS-98) and modifiers available in literature. Flood vulnerability is modelled by means of stage-damage curves developed for the study area and validated against ex-post damage claims. The method is applied to the city centre of Florence (Italy) listed as UNESCO World Heritage site since 1982. Direct multi-hazard, multi-vulnerability losses are modelled for four probabilistic scenarios. A multi-risk of 3.15 M€/year is estimated for the current situation. In case of adoption of local mitigation measures like floodproofing of basements and installation of steel tie rods, multi-risk reduces to 1.55 M€/yr. The analysis of multi-risk correlation and joint probability distribution shows that the historical evolution of the city centre, from the roman castrum followed by rebuilding in the Middle Ages, the late XIX century and the post WWII, has significantly affected multi-risk in the area. Three identified portions of the study area with a different multi-risk spatial probability distribution highlight that the urban development of the historical city influenced the flood hazard and the seismic vulnerability. The presented multi-risk workflow could be applied to other historical cities and further extended to other natural hazards.

Journey to the morpho-textural traits, microbiota, and volatilome of Ciauscolo PGI salami - Andrea Osimani; Luca Belleggia; Cristian Botta; Ilario Ferrocino; Vesna Milanović; Federica Cardinali; M. Naceur Haouet; Cristiana Garofalo; Massimo Mozzon; Roberta Foligni; Lucia Aquilanti (Food Bioscience, 2023)

Phylogeographic and population genetic structure of hound-like native dogs of the Mediterranean Basin - Francesco Perini; Irene Cardinali; Simone Ceccobelli; Anthony Gruppetta; Carlos San José; Mario Cosenza; Nicolò Musso; Amparo Martìnez; Asmaa M. Abushady; Luis V. Monteagudo; Luigi Liotta; Hovirag Lancioni; et al. (Research in Veterinary Science, 2023)

Scientists Against War: A Plea to World Leaders for Better Governance - Seithikurippu R. Pandi-Perumal; Velayudhan Mohan Kumar; Namasivayam Ganesh Pandian; Joop T. de Jong; Sudalaikannu Andiappan; Alexandru Corlateanu; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Alvhild Alette Bjørkum; et al. (Sleep and Vigilance, 2022)

Elderly as a High-risk Group during COVID-19 Pandemic: Effect of Circadian Misalignment, Sleep Dysregulation and Melatonin Administration - Daniel P. Cardinali; Gregory M. Brown; Russel J. Reiter; Seithikurippu R. Pandi-Perumal (Sleep and Vigilance, 2020)

A plant microfossil record of Late Quaternary environments and human activity from Rano Aroi and surroundings, Easter Island - M. Horrocks; W. T. Baisden; M. A. Harper; M. Marra; J. Flenley; D. Feek; S. Haoa-Cardinali; E. D. Keller; L. González Nualart; T. Edmunds Gorman (Journal of Paleolimnology, 2015)

Pollen, phytoliths, arthropods and high-resolution 14C sampling from Rano Kau, Easter Island: evidence for late Quaternary environments, ant (Formicidae) distributions and human activity - M. Horrocks; M. Marra; W. T. Baisden; J. Flenley; D. Feek; L. González Nualart; S. Haoa-Cardinali; T. Edmunds Gorman (Journal of Paleolimnology, 2013)

Organic loading rate and food-to-microorganism ratio shape prokaryotic diversity in a demo-scale up-flow anaerobic sludge blanket reactor treating domestic wastewater - Juliana Cardinali-Rezende; Juliana C. Araújo; Paulo G. S. Almeida; Carlos A. L. Chernicharo; José L. Sanz; Edmar Chartone-Souza; Andréa M. A. Nascimento (Antonie van Leeuwenhoek, 2013)

Melatonin Antioxidative Defense: Therapeutical Implications for Aging and Neurodegenerative Processes - Seithikurippu R. Pandi-Perumal; Ahmed S. BaHammam; Gregory M. Brown; D. Warren Spence; Vijay K. Bharti; Charanjit Kaur; Rüdiger Hardeland; Daniel P. Cardinali (Neurotoxicity Research, 2013)

Fossil plant remains at Rano Raraku, Easter Island’s statue quarry: evidence for past elevated lake level and ancient Polynesian agriculture - M. Horrocks; W. T. Baisden; J. Flenley; D. Feek; L. González Nualart; S. Haoa-Cardinali; T. Edmunds Gorman (Journal of Paleolimnology, 2012)

Bacterial and archaeal phylogenetic diversity associated with swine sludge from an anaerobic treatment lagoon - Juliana Cardinali-Rezende; Zelina L. Pereira; José L. Sanz; Edmar Chartone-Souza; Andréa M. A. Nascimento (World Journal of Microbiology and Biotechnology, 2012)

Microfossils of Polynesian cultigens in lake sediment cores from Rano Kau, Easter Island - M. Horrocks; W. T. Baisden; M. K. Nieuwoudt; J. Flenley; D. Feek; L. González Nualart; S. Haoa-Cardinali; T. Edmunds Gorman (Journal of Paleolimnology, 2012)

Phylogenetic and physiological characterization of organic waste-degrading bacterial communities - Juliana Cardinali-Rezende; Ana M. M. Moraes; Luis F. D. B. Colturato; Eduardo V. Carneiro; Ivanildo E. Marriel; Edmar Chartone-Souza; Andréa M. A. Nascimento (World Journal of Microbiology and Biotechnology, 2011)

Melatonin decreases the oxidative stress produced by 2,4-dichlorophenoxyacetic acid in rat cerebellar granule cells - B. Bongiovanni; P. De Lorenzi; A. Ferri; C. Konjuh; M. Rassetto; A. M. Evangelista De Duffard; D. P. Cardinali; R. Duffard (Neurotoxicity Research, 2007)

Comparative effects of melatonin and vitamin E in restoring aortic relaxation in pancreatectomized rats - C. F. Reyes-Toso; L. M. Linares; L. E. Albornoz; D. Obaya-Naredo; M. L. Wallinger; C. R. Ricci; D. P. Cardinali (Journal of Physiology and Biochemistry, 2006)

The Use of Chronobiotics in the Resynchronization of the Sleep–wake Cycle - Daniel P. Cardinali; Analía M. Furio; María P. Reyes; Luis I. Brusco (Cancer Causes & Control, 2006)

Role of melatonin in neurodegenerative diseases - V. Srinivasan; S. R. Pandi-Perumal; G. J. M. Maestroni; A. I. Esquifino; R. Hardeland; D. P. Cardinali (Neurotoxicity Research, 2005)

Comparing Landslide Maps: A Case Study in the Upper Tiber River Basin, Central Italy - F. Guzzetti; M. Cardinali; P. Reichenbach; A. Carrara (Environmental Management, 2000)

Use of GIS Technology in the Prediction and Monitoring of Landslide Hazard - A. Carrara; F. Guzzetti; M. Cardinali; P. Reichenbach (Natural Hazards, 1999)

Production of xylanases from a newly isolated alkalophilic thermophilic Bacillus sp. - M. Bataillon; A.-P. Nunes Cardinali; F. Duchiron (Biotechnology Letters, 1998)

An intercomparison between a global variable mesh and two limited area models on a case of rapid cyclogenesis - C. Cardinali; M. Caian; J. Pailleux; N. Tartaglione; A. Buzzi; A. Lavagnini; C. Transerici (Meteorology and Atmospheric Physics, 1998)